In Vivo Antiaggregatory Action of Platelet-Activating Factor in Beagle Dogs: Role for Prostacyclin - Hermán, Ferenc; Magyar, Kálmán; Filep, János G (Thrombosis and Haemostasis, 1991)
The effects of platelet-activating factor (PAF) on in vivo platelet aggregation were studied in anaesthetized beagle dogs by using the extracorporeal filter-loop technique. Intraarterial administration of PAF caused an immediate increase in filter pressure, indicating enhanced in vivo platelet aggregation. Intravenous administration of PAF (3-100 ng kg−1) resulted in a transient dose-dependent inhibition of spontaneous platelet aggregation on the filter with concomitant elevation in plasma 6-keto-PGF1Α levels. These changes were significantly attenuated by pretreatment of the animals either with BN 52021 (4 mg kg−1), a specific PAF receptor antagonist or with acetylsalicylic acid (25 mg kg−1). Intraarterial infusion of exogenous prostacyclin at concentrations similar to those observed following intravenous PAF administration, resulted in a transient inhibition of the spontaneous platelet aggregation. These data provide evidence for prostacyclin release in response to PAF, and suggest that prostacyclin may mediate the in vivo anti-aggregatory action of PAF in anaesthetized dogs.